ANALISIS PENGGUNAAN WAKTU LUANG SISWA YANG BERTEMPAT TINGGAL DI KOTA DAN DI DESA (STUDY TERHADAP SISWA DI KOTA PEKANBARU DAN DI DESA SALO ) - Nabila, Restu; Yakub, Elni; Rosmawati, Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: A learner should have intelligence and skills in many ways. One of the intelligence and skills that can be possessed by the learner is smart and skilled in utilizing the existing leisure, because the success of learners in learning is also related to how the learners take advantage of the free time that he had. The purpose of this research is to know the description of student leisure activity at home, outdoors, weekend, and semester breaks to students who attend school in town and in village. This research uses descriptive quantitative method. Data collection techniques used questionnaires. To analyze data using percentage technique. The sample in this study in the city were 135 students and in the village were 81 students. The result of the research shows that the activities done in the students' spare time at home, out of the house, weekend and semester holiday in the city are in effective category, while the villages are in the effective category. Keywords: Leisure Time, City, Village